2018
DOI: 10.3390/v10100525
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Histone H3 Acetylation in Bovine Herpesvirus 1 Replication in MDBK Cells

Abstract: During bovine herpesvirus 1 (BoHV-1) productive infection in cell cultures, partial of intranuclear viral DNA is present in nucleosomes, and viral protein VP22 associates with histones and decreases histone H4 acetylation, indicating the involvement of histone H4 acetylation in virus replication. In this study, we demonstrated that BoHV-1 infection at the late stage (at 24 h after infection) dramatically decreased histone H3 acetylation [at residues K9 (H3K9ac) and K18 (H3K18ac)], which was supported by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(58 reference statements)
3
5
0
Order By: Relevance
“…Based on these results, we assumed that if the ratio between Nrf2 and H3K9ac/H3K18ac was arbitrarily set as 1 (Nrf2 : H3K9ac/H3K18ac = 1) in the control, the ratio would be less than 1 (Nrf2 : H3K9ac/H3K18ac < 1) in the virus-infected cells, suggesting that the virus infection reduced the association ratio between Nrf2 and H3K9ac/H3K18ac. Since we have previously reported that the virus infection significantly reduced the protein levels of both H3K9ac and H3K18ac [37], the association between Nrf2 and H3K9ac/H3K18ac supported our findings that virus infection relocalized nuclear Nrf2. It is highly possible that more Nrf2 protein was relocalized to the transcriptionally active chromatin in the virus-infected cells, which is a possible mechanism to overcome adverse effects of Nrf2 depletion during virus infection.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Based on these results, we assumed that if the ratio between Nrf2 and H3K9ac/H3K18ac was arbitrarily set as 1 (Nrf2 : H3K9ac/H3K18ac = 1) in the control, the ratio would be less than 1 (Nrf2 : H3K9ac/H3K18ac < 1) in the virus-infected cells, suggesting that the virus infection reduced the association ratio between Nrf2 and H3K9ac/H3K18ac. Since we have previously reported that the virus infection significantly reduced the protein levels of both H3K9ac and H3K18ac [37], the association between Nrf2 and H3K9ac/H3K18ac supported our findings that virus infection relocalized nuclear Nrf2. It is highly possible that more Nrf2 protein was relocalized to the transcriptionally active chromatin in the virus-infected cells, which is a possible mechanism to overcome adverse effects of Nrf2 depletion during virus infection.…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that the degradation of Nrf2 protein through the ubiquitin proteasome pathway is regulated by either KEAP1-dependent or KEAP1-independent mechanisms [36]. To confirm that the ubiquitin proteasome pathway was involved in Nrf2 degradation in the virus-infected MDBK cells, the cells were exposed to proteasome inhibitor MG132 throughout viral infection as described previously [37]. We have reported that MG132 at a concentration of 1 μ M had no cytotoxicity to MDBK cells [37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence indicates that histone acetylation modification has an important role in virus infection. Several previous studies have reported virus induced changes in histone lysine acetylation sites, such as adenovirus [78], borna disease virus [31,79], Influenza virus [30,80], HIV [81], Zaire Ebolavirus [82], bovine herpesvirus [83], parvovirus [84]. In this study, nine histone lysine acetylation sites were significantly regulated, of which eight sites were down-regulated.…”
Section: Discussionsupporting
confidence: 48%